Keputusan Pembelian di TikTok Shop: Peran Trend Fashion, Celebrity Endorsement, dan Customer Rating - Khalilah; Anna Zakiyah Hastriana (Pustaka Peradaban, 2026)
The development of TikTok Shop as a leading social commerce ecosystem has established a new paradigm in consumer behavior dynamics, particularly at the stage of consideration and purchasing decision-making for fashion products. This study aims to explore and analyze in depth how fashion trends, celebrity endorsements, and customer ratings influence consumers’ purchasing decisions on the platform. Using a quantitative approach, data were collected through questionnaires distributed to active TikTok Shop users and analyzed using inferential statistical techniques to test the partial effects of each variable. Respondents selected through purposive sampling participated by providing responses based on a Likert scale. Multiple linear regression analysis was employed to examine the relationships among variables comprehensively. The findings reveal that fashion trends have a significant influence on purchasing decisions, whereas celebrity endorsements do not exert a positive impact. In contrast, customer ratings demonstrate a strong and significant contribution in encouraging consumers to make purchases. Theoretically, this study enriches the marketing literature by providing empirical evidence regarding the relative roles of these factors within the consumer decision-making model, challenging traditional assumptions about the effectiveness of celebrity endorsements, and encouraging the development of new theories that emphasize peer-to-peer social influence through customer reviews in the fashion industry. Practically, these results offer guidance for marketers and business practitioners to optimize promotional strategies by prioritizing up-to-date fashion trend campaigns and transparent customer rating systems, while reducing investment in less effective celebrity endorsements. This approach can enhance marketing efficiency, consumer satisfaction, and competitiveness in the dynamic fashion market. Perkembangan TikTok Shop sebagai ekosistem social commerce terdepan telah membentuk paradigma baru dalam dinamika perilaku konsumen, khususnya pada tahap pertimbangan dan pengambilan keputusan pembelian produk fashion. Penelitian ini bertujuan untuk mengeksplorasi dan menganalisis secaraa mendalam bagaimana trend fashion, celebrity endorsement, serta customer rating berperan dalam memengaruhi keputusan pembelian konsumen di platform tersebut. Pendekatan kuantitatif, data dikumpulkan melalui kuesioner yang ditujukan kepada pengguna aktif TikTok Shop, lalu dianalisis menggunakan teknik statistik inferensial guna menguji pengaruh parsial masing-masing variabel. Responden yang dipilih melalui purposive sampling berpartisipasi dengan memberikan tanggapan berdasarkan skala Likert. Metode analisis regresi linier berganda diterapkan untuk menguji hubungan antar variabel secara komprehensif. Temuan penelitian menunjukkan bahwa trend fashion memiliki pengaruh yang signifikan terhadap keputusan pembelian, sedangkan celebrity endorsement tidak memberikan dampak positif, namun customer rating terbukti memberikan kontribusi yang kuat dan signifikan dalam mendorong konsumen untuk membeli. Secara teoritis, penelitian ini memperkaya literatur pemasaran dengan bukti empiris tentang peran relatif faktor-faktor tersebut dalam model keputusan pembelian konsumen, menantang asumsi efektivitas tradisional dukungan celebrity, dan mendorong pengembangan teori baru yang lebih menekankan pengaruh sosial peer-to-peer melalui ulasan pelanggan di industri fashion. Secara praktis, hasil ini memberikan panduan bagi pemasar dan pelaku bisnis untuk mengoptimalkan strategi promosi dengan memprioritaskan kampanye trend fashion terkini serta sistem customer rating yang transparan, sambil mengurangi investasi pada endorsement selebriti yang kurang efektif, sehingga meningkatkan efisiensi pemasaran, kepuasan konsumen, dan daya saing di pasar fashion yang dinamis.